Nietzsche as Cultural Physician - Ahern, Daniel (My University, 1990)
From Nietzsche's early writings to those marking the end of his intellectual life~ the dynamics of what he called "physiology" permeate virtually every facet of his philosophical enterprise. In the following investigation these dynamics are explored as an interpretive key to not only the dominant themes but also the philosophical motive underlying Nietzsche's philosophy. This motive is described in terms of his diagnosis and attempted cure for the disease of nihilism. In this we maintain that Nietzsche's foremost philosophical task is that of a cultural physician. In pursuit of this theme, Nietzsche's "clinical standpoint" is explored and applied with regard to Socrates and Jesus Christ as two case studies in decadence. These two "cases" are a simultaneous physiological investigation into both the ancient Greek and Hebrew cultures. This investigation concludes with a detailed analysis of the physiological significance of the Revaluation of all Values, Eternal Recurrence, the Overman and Dionysus as integral to curing the sickness of nihilism.
Keywords: Nietzsche; culture; philosophy; Philosophy; Philosophy